Variability assessment of summer comfort conditions in social housing using in situ measurements - A. Curado (2013)
A social housing neighborhood with 4 blocks, 179 dwellings and about 450 inhabitants was recently retrofitted. An indoor climate measurement program was developed for the months of July, August and September of 2012, to evaluate the summer thermal comfort. The measurements were carried out in 24 dwellings. Indoor air temperature and relative humidity were continuously measured in the bedrooms and living rooms of the occupied dwellings. The purpose of this paper is to study thermal comfort according to the requirements presented in both EN15251 and ASHRAE-55, and the variability of the indoor air temperature using statistical analysis. The relation with parameters such as the period of measurements, the shape factor, and the occupancy was analyzed. In the end it is possible to conclude that the influence of the variability of the studied parameters on the indoor air temperature and thermal comfort, for short periods of analysis, follow a similar trend to what we have for a larger period. On the other hand the influence of the shape factor of the dwellings or the occupancy, on the indoor air temperature, reveals an effect on the measurements.